2008
DOI: 10.1021/jp7111044
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic Characterization of the Interface between Aromatic Isocyanides and Au(111):  A First-Principles Investigation

Abstract: Molecular assemblies comprising aromatic rings have received widespread attention as possible components of molecular electronic devices. An essential prerequisite to understand their stability and transport properties is the microscopic characterization of the interface formed with metallic leads. We present a comprehensive study, based on density functional theory (DFT) of the interface between the Au(111) surface and 1,4-phenylenediisocyanide, the simplest representative of aromatic isocyanides. We find tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
91
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(105 citation statements)
references
References 59 publications
11
91
3
Order By: Relevance
“…At the highest PDI exposures (180 s dosing time), the appearance of a shoulder at *2123 cm -1 , corresponding to a free isocyanide, is assigned to PDI that is adsorbed on the low-coordination gold sites in the one-dimensional chain in a vertical orientation, with one of the isocyanide groups bonded to the exposed gold atom. These species in an upright orientation have been reported several times in the literature for this systems when self-assembled monolayers were formed from solution [22][23][24][25][26].…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations
“…At the highest PDI exposures (180 s dosing time), the appearance of a shoulder at *2123 cm -1 , corresponding to a free isocyanide, is assigned to PDI that is adsorbed on the low-coordination gold sites in the one-dimensional chain in a vertical orientation, with one of the isocyanide groups bonded to the exposed gold atom. These species in an upright orientation have been reported several times in the literature for this systems when self-assembled monolayers were formed from solution [22][23][24][25][26].…”
Section: Discussionsupporting
confidence: 63%
“…In addition, the presence of a single CN vibrational mode is consistent with the proposed structure, since the isocyanide groups are symmetrically equivalent and will therefore only give rise to a single, infrared-allowed vibrational mode. The isocyanide stretching frequency is shifted from the gas-phase value of 2123 cm -1 , consistent with the formation of an isocyanide bond with the surface [22][23][24][25][26][39][40][41][42][43][44][45][46][47][48][49]. Both the C-H bending and CN stretching modes shift somewhat with coverage, and this effect is likely to be due to vibrational coupling between modes in adjacent one-dimensional chains as the coverage increases, and they come closer together.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…First, due to its high computational cost, even with today's computing power it is still far more challenging to perform GW calculations of several hundred atoms with periodic boundary conditions, as is the case for molecule-metal interfaces. [31][32][33][34] Moreover, several benchmarking studies, including work on smaller molecule-metal systems, also showed that results from perturbative GW calculations can be challenging and expensive to converge numerically. 23,35,36 Furthermore, it is by now well known that single-shot GW calculations often depend on the underlying starting point, 22,37,38 which adds additional complications for efficient GW calculations of large-scale molecule-metal interfaces and their functional properties.…”
Section: Introductionmentioning
confidence: 99%